Friction coefficient of carbon nanotube reinforced aluminium nano-composite - Abdullahi, Umma; Bello, Kamilu Adeyemi; Maleque, Md. Abdul; Yaacob, Iskandar Idris; Ali, Mohammad Yeakub; Nirmal, Umar (Ahmadu Bello University, Nigeria, 2020)
The frictional behaviour of three different nano-composites such as 1.5 wt %, 2.0 wt % and 2.5 wt % CNT –Al nano-composite materials developed by powder metallurgy process has been studied with pin-on-disc tribometer, sliding against AISI52100 steel disc. The tribological properties of pure aluminium and carbon nanotube reinforce d aluminium nano-composite were investigated and compared in this current study. Experiments were conducted using different sliding velocities of 0.5, 0.65 a nd 0.8 m/s and a normal load of 5, 7.5 and 10 N. Variations of coefficient of friction with the dur ation of rubbing at different normal loads and sliding velocities are investigated. It was revealed from the results that, coefficient of friction varies with the duration of rubbing, normal load and sliding velocities. It was clearly observed that, coeffi cient of friction increases for a certain duration of rubbing and after that it remains constant for the rest of the experimental time. Furthermore, the result shows that, coefficient of friction decreases with the increase in normal loads for aluminium wh ile for the nano material it decreases slightly for certain operating condition and remains constant in some cases. It is also observed that coefficient of friction decreased with the increased in sliding velocities for aluminium and almost remain the same for the nano material. It was further confirmed that, the developed nano material has a very high resistance to friction with low and stable coefficien t of friction which is within the range of 0.0050 - 0.01835. Further work has been recommended to be conducted on the developed material and check on the possibility of using it as a cladding material in the nuclear reactor chamber.